Detective Stories During Apartheid: H.I.E. Dhlomo as a Precursor of Drum - Fossati, Marta (Il Tolomeo, 2021)
This article aims to contribute to the discussion of English-language crime fiction by black South African writers before 1994 by exploring H.I.E. Dhlomo’s relatively overlooked contribution to the genre in the first decade of apartheid. In particular, I intend to close read three detective stories written between the late 1940s and the early 1950s by Dhlomo, namely “Village Blacksmith Tragicomedy”, “Flowers”, and “Aversion to Snakes”, and compare them with the more celebrated stories published by Arthur Maimane in the popular magazine Drum a few years later. Notwithstanding their different re-elaboration of the tropes of crime fiction, I argue that both Dhlomo and Maimane resorted to this productive strand of popular literature to reassert a claim to knowledge denied to Africans, saturating their texts with new local meanings and exceeding Western genre conventions.